Engendering cohesive software development teams: Should we focus on interdependence or autonomy?. Issue 111 (March 2018) - Kakar, Adarsh Kumar Satindarlal
Highlights: This study investigates team design issues for enhancing team cohesion. Two important considerations in team design are autonomy and interdependence. While interdependence may enhance cohesion autonomy may have a negative impact. So how can teams enhance both autonomy and interdependence without impacting team cohesion. The study finds positive goal (outcome) interdependence as the social glue in enhancing both and maximizing team cohesion. Abstract: Empirical evidence suggests that both autonomy and interdependence are important considerations in team design. But how do interdependence and autonomy affect team cohesiveness, an important antecedent of team performance? The results of this multi-year study with software development projects show that task interdependence and task autonomy have both synergistic and antagonistic impacts on team cohesiveness. At high levels of outcome (goal) interdependence, task autonomy and task interdependence have a synergistic impact on team cohesion, while at low levels of outcome interdependence, task autonomy and task interdependence have an antagonistic impact on team cohesion. Further, taylorist teams showed lower cohesiveness compared to agile teams.